Evaluar el sistema de control interno al área contable - financiera y suincidencia enla rentabilidad de la Agrícola Peñaherrera Martínez, año 2012. - Macías Mena, Magna Liliana (2015)
The research was conducted in order to evaluate the Internal Control System to Accounting and Financial Area and its impact on the profitability of agricultural Peñaherrera Martinez 2012. It was necessary for it to apply inductive methods to describe the particular to the general problem and method, deductive from the general to the particular, as well as the scientific method, changing techniques and instruments such as internal control questionnaire focused on the five was applied COSO components I, to evaluate the control areas and determine the level of trust and risk level of the farm business. It was determined that there occurs an ineffective controls, the need to apply financial accounting procedures to monitor losses, mismanagement and lack of planning so what is the current situation of the company to be variations on the information as far as accounting is concerned, so the "Agricultural Peñaherrera Martinez" required the procedures which aims to control and verify the existence of cash. Being a family farm is the same owner in charge of managing resources, without an accounting and financial system, and not apply controls and procedures, enabling it to verify what your current situation. The internal control report was based on the results of internal control, findings, consisting of the same findings, conclusions and recommendations to be discussed by management and commissioning execution thereof to improve processes within the company.